Lateritic mineral loading process'influence in the conveyors (2007)
The conveyors used in the laterític  mineral loading's process of the "Ernesto Che Guevara Company", present irregularities that cause the deterioration of the band  and its gradual destruction . Here the resistance  in the load points is determined considering the size of the pieces, the form and the fall height. This allows to find the lenght of the load point, in the speed and  the displacement experimentally way for the latiric mineral.